Glucagon-Like Receptor 1 Agonists and DPP-4 Inhibitors: Potential Therapies for the Treatment of Stroke. Issue 5 (May 2015) - Darsalia, Vladimer; Larsson, Martin; Nathanson, David; Klein, Thomas; Nyström, Thomas; Patrone, Cesare
During the past decades, candidate drugs that have shown neuroprotective efficacy in the preclinical setting have failed in clinical stroke trials. As a result, no treatment for stroke based on neuroprotection is available today. The activation of the glucagon-like peptide 1 receptor (GLP-1) for reducing stroke damage is a relatively novel concept that has shown neuroprotective effects in animal models. In addition, clinical studies are currently ongoing. Herein, we review this emerging research field and discuss the next milestones to be achieved to develop a novel antistroke therapy.